To Make Live and Let Die. "The Part of the Crimes" in the Novel 2666 of Roberto Bolaño. (Palimpsesto, 2017)
The present article addresses the fourth part of the novel 2666 titled "The part of the crimes" of the Chilean writer Roberto Bolaño, where the violence to the women in the border context of the present neoliberal societies is presented with intensity. From the crimes described, the novel allows us to recognize the conditions of pauperization of the work of the Maquilas in the transnational market society and women within that space no longer defined from the nation-state, but from the indeterminate space of the flows of people and products, which for Foucault constitutes a biopolitics of making live and letting dies. At the same time, according to its narrative form, the novel allows to recognize, following Benjamin with his notion of allegory, a political proposal defined by an aesthetic of horror and violence.
Keywords: Bolaño; Feminicide; Allegory; Maquila; Foucault